2014
DOI: 10.4274/tjh.2013.0090
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Large B-Cell Lymphoma Diagnosed on Prostate Biopsy: A Case Report

Abstract: Intravascular large B-cell lymphoma (IVLBCL) is a very rare type of non-Hodgkin lymphoma, usually affecting elderly patients and characterized by selective infiltration of neoplastic cells within blood vessels’ lumina. IVLBCL diagnosed with prostatic involvement is extremely rare. We report a patient of 65 years old, having mostly neurological complaints but diagnosed with IVLBCL upon histopathological examination of transurethral prostate resection material, which revealed large neoplastic cell infiltration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Moreover, CT showed ground-glass opacities of lung, hepatomegaly, and enlargement of adrenals. Some previous studies showed high frequency of neurological abnormalities on brain magnetic resonance imaging (MRI), and these abnormal findings appeared to relate to ischemic changes of small brain capillaries due to neoplastic lymphoma cells (27)(28)(29)(30)(31)(32)(33)(34)(35). However all patients in four new cases did not present neurological symptoms, and thus, brain MRI was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CT showed ground-glass opacities of lung, hepatomegaly, and enlargement of adrenals. Some previous studies showed high frequency of neurological abnormalities on brain magnetic resonance imaging (MRI), and these abnormal findings appeared to relate to ischemic changes of small brain capillaries due to neoplastic lymphoma cells (27)(28)(29)(30)(31)(32)(33)(34)(35). However all patients in four new cases did not present neurological symptoms, and thus, brain MRI was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated LDH levels, fever of unknown origin, and unexplained neurological symptoms in elderly patients should raise the suspicious of lymphoma. 4,[6][7][8] It should be differentiated from adenocarcinoma of prostate and secondary metastasis as the treatment protocol varies. Biopsy and immunohistochemical assessment are the gold standard for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[8] The prostate has been reported as one of the involved sites by IVLBCL in few cases. [9][10][11] However, primary prostate IVLBCL was reported only in three cases according to a comprehensive literature search from the electronic databases PubMed with the keywords of "intravascular large B cell lymphoma" and "prostate". [12][13][14] It is lack of the accurate diagnosis and treatment strategy of primary prostate IVLBCL until now.…”
Section: Introductionmentioning
confidence: 99%